PENGARUH SELF ESTEEM dan SELF EFFICACY TERHADAP KINERJA KARYAWAN - Andriyanti; Putri Kartika Mariska; Diajeng Sekar Ramadhany Ernanda (Program Studi Akuntansi IKOPIN, 2022)
This study aims to determine the effect of self esteem and self efficacy on employee performance. This research was conducted to employee in one of the islamic banks in Bandung with total population of 68 people. The sampling technique used is a saturated sample. The independent variables in this study are self esteem dan self efficacy, while the dependent variables is employee performance. Measurement of variables using a Likert scale. For data processing using SPSS version 20 for Windows. Data analysis used multiple linear regression analysis. The result showed that self esteem and self efficacyhad a significant effect on employee performance